Pengaruh Fasilitas dan Kualitas Pelayanan terhadap Kepuasan Pengunjung di Konser Musik Blackpink “Born Pink World Tour Jakarta 2023” - Tasya Dewi, Vanissa; Supriyadi, Tedi; Pratama, Gilang (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
The Blackpink "Born Pink World Tour Jakarta 2023" concert, organized by iMe Indonesia as the promoter, faced a flood of criticism from attendees regarding issues such as double tickets, discrepancies in the number of seating facilities, and complaints about staff service that was perceived as unfriendly and slow in resolving problems. This study aims to test the hypothesis regarding the relationship between facilities and service quality at the concert and the level of attendee satisfaction. The research method used is quantitative with a survey design. The survey technique was employed to collect primary data by providing respondents with indicator statements through an online questionnaire. The research sample consisted of one hundred respondents who were Blackpink fans attending the concert. The data obtained were processed using IBM SPSS version 26. Data analysis was performed using descriptive analysis and multiple linear regression. The results of the study indicate that the independent variables of Facilities (X1) and Service Quality (X2) simultaneously affect the dependent variable of Attendee Satisfaction (Y). The practical implication of this study is the importance for promoters to pay attention to the quality of facilities and services to enhance visitor satisfaction at music concerts.